1000MPa-grade cerium-containing high-strength steel welding wire, preparation method thereof and application of 1000MPa-grade cerium-containing high-strength steel welding wire in water-power engineering
By precisely controlling the chemical composition and preparation process of 1000MPa grade cerium-containing high-strength steel welding wire, the problems of low-temperature toughness and cracking of high-strength steel welding wire have been solved, achieving high-efficiency welding performance and cost reduction, meeting the needs of large-scale hydropower projects.
Patent Information
- Application Number
- CN202411507449.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
AI Technical Summary
The 1000MPa grade high-strength steel welding wire has performance problems such as low low-temperature toughness and easy cracking at low temperatures, which cannot meet the welding requirements of large-scale hydropower projects.
A 1000MPa grade cerium-containing high-strength steel welding wire was designed. By precisely controlling the chemical composition and preparation process, including smelting, electroslag remelting, forging, hot rolling of wire rod, drawing and surface treatment, the finished welding wire was prepared and the welding performance was optimized.
It improves the low-temperature toughness and crack resistance of welding wire, reduces production costs, achieves the substitution of imported welding materials, meets the application requirements of high-strength steel in large-scale hydropower projects, and enhances independent innovation capabilities.
Smart Images

Figure BDA0005104406060000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of welding, and in particular relates to a 1000MPa-grade cerium-containing high-strength steel welding wire and a preparation method thereof, and application thereof in hydropower engineering. Background Art
[0002] As a clean and renewable energy source, hydropower plays an important role in today's industrial field. With the continuous growth of society's demand for energy and the increasing attention to environmental protection, renewable energy has been vigorously promoted, and hydropower generation technology has also been continuously innovated. In this process, the construction scale and number of large and giant hydropower stations have continued to increase, and the requirements for related materials and technologies have become increasingly stringent. In the construction of large and giant hydropower stations, high-strength steel welding wire plays a vital role. The key components in large-capacity hydropower projects must be able to withstand the impact of high head, high speed and high efficiency, such as forging welding of impact turbine volutes, water diversion pressure pipelines, bifurcated pipes, etc. However, the current 1000MPa-grade high-strength steel welding wire has low low-temperature toughness and performance problems such as easy cracking at low temperatures, which cannot meet the welding requirements of such large-capacity hydropower projects. Therefore, in order to solve these problems and promote the development of large-capacity hydropower projects, it is necessary to design a 1000MPa-grade high-toughness high-strength steel welding wire to overcome the problems of low low-temperature toughness and cracking at low temperatures. Summary of the invention
[0003] The purpose of the present invention is to solve the performance problems of low low-temperature toughness and easy cracking of 1000MPa high-strength steel welding wire at low temperature. The present invention provides a 1000MPa cerium-containing high-strength steel welding wire and a preparation method thereof.
[0004] The technical solution of the present invention is as follows:
[0005] One of the purposes of the present invention is to provide a 1000MPa grade cerium-containing high-strength steel welding wire, the chemical composition of the welding wire comprising, by weight percentage: C 0.05-0.15%, Si 0.4-1.0%, Mn 1.2-2.0%, Cr 0.2-1.0%, Ni2.8-4.3%, Mo 0.30-1.0%, Ti 0.02-0.2%, Cu 0.1-0.5%, Ce 0.1-0.8%, S≤0.007%, P≤0.008%, and the balance being Fe and impurities.
[0006] It is further defined that the chemical composition of the welding wire includes, by weight percentage: C 0.06-0.14%, Si 0.5-1.0%, Mn 1.3-1.9%, Cr 0.3-1.0%, Ni 3.0-4.2%, Mo 0.38-1.0%, Ti 0.03-0.18%, Cu 0.1-0.4%, Ce 0.1-0.8%, S≤0.007%, P≤0.008%, and the balance is Fe and impurities.
[0007] The second object of the present invention is to provide a method for preparing a 1000MPa grade cerium-containing high-strength steel welding wire, the method comprising:
[0008] S1: sequentially smelting, electroslag remelting, forging, and hot-rolling the welding wire raw materials to obtain wire rods;
[0009] S2: laying out the wire rod, peeling it, grinding it with a sand belt, and then drawing it with a roller die to obtain the finished product;
[0010] S3: The finished product is ultrasonically cleaned, blown dry, and subjected to surface rust prevention treatment. It is then wound in dense layers to obtain welding wire.
[0011] It is further defined that the wire rod diameter in S1 is Φ5.5 mm.
[0012] It is further defined that the drawing speed of S2 is 200-300 m / min.
[0013] It is further defined that the diameter of the finished product in S2 is Φ1.2 mm.
[0014] It is further defined that the finished diameter tolerance of S2 is ±0.04 mm.
[0015] It is further defined that the S2 roller die drawing is a 14-pass continuous drawing.
[0016] It is further defined that the surface anti-rust treatment of S3 is copper plating or surface coating with anti-rust oil.
[0017] The third object of the present invention is to provide a 1000MPa grade cerium-containing high-strength steel welding wire for use in hydropower projects.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) The high-strength steel welding wire of the present invention effectively reduces the burning loss of Ce during welding by precisely controlling the weight percentage of various elements in the welding wire, so that Ce can still maintain a high transition coefficient under the condition of large line energy heat input, thereby greatly reducing the production cost of such high-strength steel welding wire containing Ce.
[0020] (2) The high-strength steel welding wire of the present invention is prepared into a finished welding wire through smelting, electroslag remelting, wire rod hot rolling, drawing, cleaning, oiling or copper plating. The properties of the deposited metal of the welding wire are equivalent to those of imported welding materials, which can achieve import substitution, greatly reduce the construction cost of high-strength steel application fields such as large hydropower stations and pumped storage power stations, and can also be applied to various engineering projects applicable to 1000MPa level. At the same time, the present invention can fully meet the specific needs of the engineering machinery industry for high-strength steel welding wire, has significant economic and social benefits, helps to promote the development of related industries, reduce dependence on imported products, and improve the technical level and independent innovation capabilities in the field of high-strength steel welding. DETAILED DESCRIPTION
[0021] In the present invention, the composition range of 1000MPa grade cerium-containing high-strength steel welding wire is designed for the following reasons:
[0022] C: 0.05-0.15%; C is mainly used to adjust the strength and hardness of high-strength steel welding wire. In high-strength steel welding wire, if the C content is reduced, the strength and hardness of the deposited metal will decrease. However, the strength of the deposited metal cannot be improved by simply relying on the C element. When the C content in the high-strength steel welding wire increases, its carbon equivalent will also increase accordingly, which will lead to increased welding crack sensitivity and deterioration of welding performance. In view of this, in the present invention, the C content is controlled at 0.05-0.15%.
[0023] Si: 0.4-1.0%; Si is a good deoxidizer in welding wire. It can combine with O to form oxides, thereby reducing the O content in the weld, reducing the generation of welding defects such as pores and slag inclusions, and thus improving the performance of the deposited metal. Too high Si content will make the deposited metal structure coarse, leading to grain boundary embrittlement, thereby reducing the impact resistance of the deposited metal at low temperatures and the fatigue performance of the welded structure. In view of this, in the present invention, the Si content is controlled at 0.4-1.0%.
[0024] Mn: 1.2-2.0%; Mn can effectively reduce the oxide content in the deposited metal, reduce the influence of O on the deposited metal, improve the purity of the deposited metal, and improve the toughness and plasticity of the deposited metal. When the Mn content is too high, it will promote the formation of more hard phases in the deposited metal. The presence of these hard phases will reduce the deformation ability of the deposited metal, resulting in poor toughness and plasticity. In view of this, in the present invention, the Mn content is controlled at 1.2-2.0%.
[0025] S≤0.007%, P≤0.008%; when the S content is too high, a low melting point compound is formed, resulting in poor crack resistance. When the P content is too high, the toughness of the deposited metal is significantly reduced, so the S and P contents should be reduced as much as possible. In view of this, in the present invention, S≤0.007%, P≤0.008% are strictly controlled by wire refining.
[0026] Cr: 0.2-1.0%; Cr can make the crystal structure of the deposited metal more compact through solid solution strengthening and precipitation strengthening, hinder dislocation movement, and improve the strength of the deposited metal. In view of this, in the present invention, the Cr content is controlled to 0.2-1.0%.
[0027] Ni: 2.8-4.3%; A proper amount of Ni can effectively reduce the ductile-brittle transition temperature of the deposited metal and improve the impact toughness of the deposited metal at low temperatures; Ni can also improve the strength and hardness of the deposited metal through solid solution strengthening and grain refinement. Too high a Ni content will change the crystal structure of the deposited metal and increase its brittle tendency, which is detrimental to the plasticity and toughness of the deposited metal. In view of this, in the present invention, the Ni content is controlled at 2.8-4.3%.
[0028] Mo: 0.3-1.0%; An appropriate amount of Mo can significantly improve the strength of the deposited metal by solid solution strengthening, precipitation strengthening, etc. At the same time, Mo can refine the grains and reduce the content of inclusions in the deposited metal, thereby reducing the ductile-brittle transition temperature of the deposited metal and improving the toughness of the deposited metal at low temperatures. In view of this, in the present invention, the Mo content is controlled at 0.3-1.0%.
[0029] Ti: 0.02-0.2%; During the crystallization process of the deposited metal, Ti can promote grain refinement and improve the strength and toughness of the deposited metal. Ti atoms dissolved in the high-strength steel matrix will cause lattice distortion, increase the resistance to dislocation movement, and make it more difficult for dislocations to move in the deposited metal, thereby improving the strength of the deposited metal. In view of this, in the present invention, the Ti content is controlled to 0.02-0.2%.
[0030] Cu: 0.1-0.5%; Cu can be dissolved in the matrix of the deposited metal, causing lattice distortion and producing a solid solution strengthening effect; fine Cu-rich phase particles will play a role in precipitation strengthening in the deposited metal, hindering the movement of dislocations and improving the strength and hardness of the deposited metal. In view of this, in the present invention, the Cu content is controlled at 0.1-0.5%.
[0031] Ce: 0.1-0.8%; Ce can react with elements such as O and S in low-alloy high-strength steel to form high-melting-point compounds. These compounds will precipitate preferentially during the solidification of the molten droplet, reducing the content of inclusions in the deposited metal and improving the purity of the deposited metal. The reduction of inclusions in the deposited metal can reduce the brittleness of the steel and improve the toughness and impact resistance of the deposited metal. During the solidification of the molten droplet, Ce can act as a heterogeneous nucleation core to promote nucleation and play a role in grain refinement. On the one hand, the refined grains make the crack propagation path more tortuous, consume more energy, and improve the toughness of the deposited metal; on the other hand, rare earth cerium can change the morphology of inclusions in the deposited metal, transforming it from irregular shapes such as long strips and sharp corners to spherical or nearly spherical shapes, reducing the adverse effects of inclusions on the toughness of the deposited metal.
[0032] During the welding process, Ce will evaporate and enter the arc atmosphere, react with the gas molecules in the arc, change the composition of the arc atmosphere, and affect the ionization degree of the arc atmosphere. Since Ce has good electrical conductivity, it can reduce the jitter and instability of the arc. This helps to optimize the droplet transition form of high-strength steel welding wire, making the droplets smaller and more uniform, the transition smoother, and greatly improving the droplet transition frequency. The welding arc is more stable, reducing defects such as spatter and pores during welding, thereby improving the quality of the weld. In view of this, in the present invention, the Ce content is controlled at 0.1-0.8%.
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.
[0035] Embodiment 1:
[0036] Welding wire diameter: 1.2mm. The chemical composition of the welding wire material is C 0.14%, Si 0.85%, Mn1.41%, S 0.0042%, P 0.006%, Cr 0.85%, Ni 3.75%, Mo 0.85%, Ti 0.15%, Cu0.31%, Ce 0.2% by weight, and the balance is Fe and impurities.
[0037] Preparation of welding wire: The wire rod with the above chemical composition and a diameter of Ф5.5mm is obtained through smelting, electroslag remelting, forging, high-speed hot rolling and other processes, and then after wire laying, shelling and belt grinding, the wire rod is reduced in diameter by 14 continuous drawing processes at a speed of 200-300m / min by a roller die + mold to obtain a welding wire with a diameter of Ф1.2mm. The welding wire is cleaned online by ultrasonic wave, blown dry, and coated with anti-rust oil on the surface. After being taken up by an I-shaped wheel, it is wound in dense layers to obtain a finished welding wire.
[0038] The welding wire prepared in this embodiment is used to weld a joint test plate of 1000MPa grade high-strength steel. The size of the welding test plate is 300mm×300mm×20mm. The iron grinding test is carried out according to the standard GB 4675.1-1984 "Test method for cracks of inclined Y-groove welding", and the plug test and cold crack sensitivity evaluation test are carried out according to the standard GB 9446-1988 "Test method for cold cracks of plugs for welding". The impact performance test of the weld deposited metal is carried out according to the provisions of GB / T 2650-2022, and the tensile performance test is carried out according to the provisions of GB / T 2652-2022.
[0039] The welding parameters of this embodiment are: the groove form is a 45° V-groove, the gas flow rate during welding is 20L / min, and the volume ratio of the protective gas is 15% CO2+85% Ar; the welding current type is DC reverse connection, the welding current is 275A, the welding voltage is 30V, the welding speed is 330cm / min, the preheating temperature is 100°C, and the interpass temperature is 165°C.
[0040] Embodiment 2:
[0041] The difference from Example 1 is that the chemical composition of the welding wire material is C 0.013%, Si 0.79%, Mn 1.46%, S 0.0056%, P 0.007%, Cr 0.81%, Ni 3.8%, Mo 0.78%, Ti 0.16%, Cu 0.35%, Ce 0.6%, and the balance is Fe and impurities.
[0042] The remaining operation steps and parameter settings are the same as those in Example 1.
[0043] Embodiment 3:
[0044] The difference from Example 1 is that the chemical composition of the welding wire material is C 0.014%, Si 0.84%, Mn 1.44%, S 0.0053%, P 0.0059%, Cr 0.9%, Ni 3.9%, Mo 0.88%, Ti 0.14%, Cu 0.28%, Ce 0.4%, and the balance is Fe and impurities.
[0045] Comparative Example 1:
[0046] The difference from Example 1 is that the chemical composition of the welding wire material is C 0.014%, Si 0.80%, Mn 1.50%, S 0.0051%, P 0.0072%, Cr 0.79%, Ni 3.70%, Mo 0.80%, Ti 0.15%, Cu 0.32%, and the balance is Fe and impurities.
[0047] Comparative Example 2:
[0048] The difference from Example 1 is that the chemical composition of the welding wire material is C 0.013%, Si 0.87%, Mn 1.54%, S 0.0058%, P 0.0068%, Cr 0.81%, Ni 3.6%, Mo 0.76%, Ti 0.13%, Cu 0.27%, and the balance is Fe and impurities.
[0049] Table 1 Performance test of Examples 1-3 and Comparative Examples 1-2
[0050]
[0051] It can be seen from Table 1 that Examples 1-3 are superior to Comparative Examples 1-2 in all aspects of performance, especially in terms of the impact absorption energy of -40°C impact performance, Examples 1-3 are all higher than 75KV2 / (J), while Comparative Examples 1-2 are all lower than 45KV2 / (J). No cracks are generated in Examples 1-3 in the bending performance test and the cold crack sensitivity test, while Comparative Example 2 has cracks in the bending performance test, and Comparative Example 1 has cracks in the cold crack sensitivity test. Therefore, the welding wire of the present invention can overcome the problems of low low-temperature toughness and low-temperature cracking of 1000MPa grade high-strength steel welding wire.
[0052] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A 1000MPa grade cerium-containing high-strength steel welding wire, characterized in that: The chemical composition includes by weight percentage: C 0.05-0.15%, Si 0.4-1.0%, Mn 1.2-2.0%, Cr 0.2-1.0%, Ni 2.8-4.3%, Mo 0.30-1.0%, Ti 0.02-0.2%, Cu 0.1-0.5%, Ce 0.1-0.8%, S≤0.007%, P≤0.008%, and the balance is Fe and impurities.
2. The 1000MPa grade cerium-containing high-strength steel welding wire according to claim 1, characterized in that: The chemical composition includes by weight percentage: C 0.06-0.14%, Si 0.5-1.0%, Mn 1.3-1.9%, Cr 0.3-1.0%, Ni 3.0-4.2%, Mo 0.38-1.0%, Ti 0.03-0.18%, Cu 0.1-0.4%, Ce 0.1-0.8%, S≤0.007%, P≤0.008%, and the balance is Fe and impurities.
3. The method for preparing the 1000MPa grade cerium-containing high-strength steel welding wire according to claim 1 or 2, characterized in that: The method: S1: sequentially smelting, electroslag remelting, forging, and hot-rolling the welding wire raw materials to obtain wire rods; S2: laying out the wire rod, peeling it, grinding it with a sand belt, and then drawing it with a roller die to obtain the finished product; S3: The finished product is ultrasonically cleaned, blown dry, and subjected to surface rust prevention treatment. It is then wound in dense layers to obtain welding wire.
4. The preparation method according to claim 3, characterized in that: The diameter of the wire rod in S1 is Ф5.5mm.
5. The preparation method according to claim 3, characterized in that: The drawing speed of S2 is 200-300 m / min.
6. The preparation method according to claim 3, characterized in that: The finished product diameter of S2 is Ф1.2mm.
7. The preparation method according to claim 3, characterized in that: The finished diameter tolerance of S2 is ±0.04mm.
8. The preparation method according to claim 3, characterized in that: S2 roller die drawing is a 14-pass continuous drawing process.
9. The preparation method according to claim 3, characterized in that: The surface anti-rust treatment of S3 is copper plating or surface coating with anti-rust oil.
10. Application of the welding wire according to claim 1 or 2 in hydropower engineering.
Citation Information
Cited By
Method for improving compression strength of high-strength welding wire
CN120551634A